2021
DOI: 10.3389/fmicb.2021.642549
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Administration of Bifidobacterium longum subsp. infantis CECT 7210 and Lactobacillus rhamnosus HN001 and Their Synbiotic Combination With Galacto-Oligosaccharides Against Enterotoxigenic Escherichia coli F4 in an Early Weaned Piglet Model

Abstract: We evaluated the potential of multi-strain probiotic (Bifidobacterium longum subsp. infantis CECT 7210 and Lactobacillus rhamnosus HN001) with or without galacto-oligosaccharides against enterotoxigenic Escherichia coli (ETEC) F4 infection in post-weaning pigs. Ninety-six piglets were distributed into 32 pens assigned to five treatments: one non-challenged (CTR+) and four challenged: control diet (CTR−), with probiotics (>3 × 1010 CFU/kg body weight each, PRO), prebiotic (5%, PRE), or their combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 87 publications
2
10
0
Order By: Relevance
“…infantis CECT 7210—has proven to be effective in reducing Salmonella loads in piglets in previous works ( Barba-Vidal et al, 2017 ). Interestingly, the former strain administered together with L. rhamnosus HN001 was also capable of diminishing Salmonella and ETEC F4 presence as shown by our research group in the past ( Rodríguez-Sorrento et al, 2020 , 2021 ). Nevertheless, in the present trial, combining this probiotic with inulin and FOS was unable to reduce Salmonella excretion, suggesting that the combination of this Bifidobacterium strain with these prebiotics does not improve its power to fight the pathogen.…”
Section: Discussionsupporting
confidence: 55%
“…infantis CECT 7210—has proven to be effective in reducing Salmonella loads in piglets in previous works ( Barba-Vidal et al, 2017 ). Interestingly, the former strain administered together with L. rhamnosus HN001 was also capable of diminishing Salmonella and ETEC F4 presence as shown by our research group in the past ( Rodríguez-Sorrento et al, 2020 , 2021 ). Nevertheless, in the present trial, combining this probiotic with inulin and FOS was unable to reduce Salmonella excretion, suggesting that the combination of this Bifidobacterium strain with these prebiotics does not improve its power to fight the pathogen.…”
Section: Discussionsupporting
confidence: 55%
“…Barba-Vidal et al and Rodrigues-Sorrento et al reported a reduction in colonic ammonia levels after supplementation with Bifidobacterium longum subsp. infantis in piglets challenged with ETEC K88 [189] or ETEC F4 [190] Meanwhile, probiotic feeding in pigs reduces skatole concentrations, as observed in multiple studies [177,180,191]. Similarly, supplementation of either Bacillus subtilis DSM 32315 with xylooligosaccharides (XOS) or a combination of Lactobacillus plantarum B90 and Saccharomyces cerevisiae P11 decreased indole concentrations [176,180].…”
Section: Influence Of Probiotics Supplementation On Mi-crobial Metabo...mentioning
confidence: 84%
“…For the trial, the enterotoxigenic Escherichia coli (ETEC) F4 strain COLI30/14-3 used (positive for virulence factors F4ab, F4ac, LT, STb, and EAST1 and negative for K99, F6, F18, F41, STa, VT1, VT2, and EAE) was isolated from feces of a 14-week-old pig from a farm with a clinical course of colibacillosis and provided by the Veterinary Laboratory of Diagnosis of Infectious Diseases of UAB. This strain was actually used with the same purpose in previous studies of our group [22]. The oral inoculums were prepared by an overnight incubation at 37 • C in Brain Heart Infusion (BHI) with slow agitation (1× g) in an orbital incubator.…”
Section: Bacterial Strainmentioning
confidence: 99%